Zooming On All Actors: Automatic Focus+Context Split Screen Video Generation. (23rd May 2017) - Kumar, Moneish; Gandhi, Vineet; Ronfard, Remi; Gleicher, Michael
Abstract: Recordings of stage performances are easy to capture with a high‐resolution camera, but are difficult to watch because the actors' faces are too small. We present an approach to automatically create a split screen video that transforms these recordings to show both the context of the scene as well as close‐up details of the actors. Given a static recording of a stage performance and tracking information about the actors positions, our system generates videos showing a focus+context view based on computed close‐up camera motions using crop‐and zoom. The key to our approach is to compute these camera motions such that they are cinematically valid close‐ups and to ensure that the set of views of the different actors are properly coordinated and presented. We pose the computation of camera motions as convex optimization that creates detailed views and smooth movements, subject to cinematic constraints such as not cutting faces with the edge of the frame. Additional constraints link the close up views of each actor, causing them to merge seamlessly when actors are close. Generated views are placed in a resulting layout that preserves the spatial relationships between actors. We demonstrate our results on a variety of staged theater and dance performances.